2018
DOI: 10.1007/s12298-018-0538-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and spatial genetic structure of natural Moroccan Quercus susber L. assessed by ISSR markers for conservation

Abstract: Morocco is one of the most important regions of the world in terms of L. number and variation. This species is in decline due to several factors, which can lead to permanent loss of this resource. It would be essential to evaluate the genetic diversity in order to conserve maximum genetic variability of this species. The genetic diversity and differentiation of 16 sites from five regions representing the entire range of Moroccan Cork Oak were assessed. Twenty-three ISSR primers used generated 985 polymorphic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…The difference in the markers in formativeness and performance between our study and that of Domyati et al 29 could be the results of the difference in the primers sequences used and the genetic background of the populations tested. Nevertheless, the level of polymorphism found in our study is consistent with that reported for similar long-lived perennial species such as Cork Oak 31 and Baobab (Adansonia digitata) 32 . Moreover, natural populations of B. aegyptiaca in the Saharan zone are subjected to several anthropogenic (the need of wood for fuel), animal (mainly dromedary grazing) and environmental (extreme aridity) pressures, that could be probably the cause of the low observed variability.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The difference in the markers in formativeness and performance between our study and that of Domyati et al 29 could be the results of the difference in the primers sequences used and the genetic background of the populations tested. Nevertheless, the level of polymorphism found in our study is consistent with that reported for similar long-lived perennial species such as Cork Oak 31 and Baobab (Adansonia digitata) 32 . Moreover, natural populations of B. aegyptiaca in the Saharan zone are subjected to several anthropogenic (the need of wood for fuel), animal (mainly dromedary grazing) and environmental (extreme aridity) pressures, that could be probably the cause of the low observed variability.…”
Section: Discussionsupporting
confidence: 92%
“…The difference in the markers in formativeness and performance between our study and that of Domyati et al 29 could be the results of the difference in the primers sequences used and the genetic background of the populations tested. Nevertheless, the level of polymorphism found in our study is consistent with that reported for similar long-lived perennial species such as Cork Oak 31 and Baobab ( Adansonia digitata ) 32 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For some tree species, previous reports have suggested that a sample size of 25-29 [38] or less than 30 [39] per population should be sufficient. In contrast, numerous lines of evidence have demonstrated that the parameters of genetic diversity can be accurately estimated through the study of small populations with less than 10 individuals, as previously reported for Quercus susber L. [40] and Eucalyptus occidentalis Endl. [41].…”
Section: Discussionmentioning
confidence: 92%
“…Although the reduced accuracy of estimation of genetic diversity using dominant markers was reported, it has been well documented that ISSR is a reliable technique for detecting DNA polymorphisms and assessing genetic diversity of many woody plant species [16][17][18]. Even though no ISSR analysis study has been carried out on K. latifolia, numerous similar researches have been conducted on other two genera, Rhododendron and Vaccinium, in Ericaceae.…”
Section: Effectiveness Of Issr In K Latifoliamentioning
confidence: 99%